1996
DOI: 10.1073/pnas.93.23.13250
|View full text |Cite
|
Sign up to set email alerts
|

The 3′-untranslated region of CaMKIIα is a cis-acting signal for the localization and translation of mRNA in dendrites

Abstract: Neuronal signaling requires that synaptic proteins be appropriately localized within the cell and regulated there. In mammalian neurons, polyribosomes are found not just in the cell body, but also in dendrites where they are concentrated within or beneath the dendritic spine. The ␣ subunit of Ca 2؉ -calmodulin-dependent protein kinase II (CaMKII␣) is one of only five mRNAs known to be present within the dendrites, as well as in the soma of neurons. This targeted subcellular localization of the mRNA for CaMKII␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
228
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(239 citation statements)
references
References 29 publications
7
228
1
3
Order By: Relevance
“…Active protein synthesis has been demonstrated in dendrites in vitro (Torre and Steward, 1992;Crino and Eberwine, 1996) and in vivo (Mayford et al, 1996). Neurotrophin-induced synaptic plasticity in the hippocampus has been reported to depend on local protein synthesis in CA1 pyramidal cell dendrites (Kang and Schuman, 1996).…”
Section: Abstract: Neuronal Bc1 Rna; Rna Transport; Dendrites; Targementioning
confidence: 99%
“…Active protein synthesis has been demonstrated in dendrites in vitro (Torre and Steward, 1992;Crino and Eberwine, 1996) and in vivo (Mayford et al, 1996). Neurotrophin-induced synaptic plasticity in the hippocampus has been reported to depend on local protein synthesis in CA1 pyramidal cell dendrites (Kang and Schuman, 1996).…”
Section: Abstract: Neuronal Bc1 Rna; Rna Transport; Dendrites; Targementioning
confidence: 99%
“…As an initial attempt to examine the role of G proteins and the cAMP/PKA system in sensorimotor gating, we measured PPI in wild-type and transgenic mice that express a constitutively active form of G s α (G s α*) (Abel et al, 1997a;Wand et al, 2001) and transgenic mice that express a dominant-negative form of protein kinase A, R(AB) (Abel et al, 1997b). Both transgenes are under the control of the CaMKIIα promoter that drives expression in neurons within forebrain areas including the neocortex, olfactory bulb, hippocampus, striatum, and amygdala (Mayford et al, 1996). These transgenic mice exhibited selective impairments in hippocampus-dependent forms of memory and alterations in hippocampal synaptic physiology (Abel et al, 1997a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The dendritic trafficking of this transcript and the role of local translated CaMKIIa in synaptic plasticity events has been widely studied (Mayford et al, 1996;Miller et al, 2002;Ouyang et al, 1999). Other relatively abundant mRNAs in the neuropil region included the transcripts encoding for Shank1, PSD95 (postsynaptic density protein 95), Dendrin and MAP (microtubule-associated protein) 1A (Cajigas et al, 2012), all of them previously reported as dendritic mRNAs (Bockers et al, 2004;Herb et al, 1997;Muddashetty et al, 2007;Tucker et al, 1989).…”
Section: Cis-acting Elements and Mrna Transport Into Dendritesmentioning
confidence: 99%